Apparatus development for detecting the freshness of chicken meat using TCS 3200, PH-98108, and MOS gas sensors - Nastiti, P. W.; Bintoro, N.; Karyadi, J. N. W.; Rahayoe, S.; Saputro, A. D. (Rynnye Lyan Resources, 2023)
Meat can be determined as a muscle that has entered a rigour mortis state. Due to its high nutritional content, the quality of chicken meat quickly decreased. The changes in meat colour, pH, and metabolite gas production, especially ammonia and hydrogen sulfide, are the typical indicators for meat degradation. This research aimed to design and build an apparatus to evaluate the freshness of the chicken meat displayed for sale or storage. In the following study, four different sensors, including TCS 3200 colour sensor, Metal Oxide Semiconductor (MOS) gas sensors (MQ 136, MQ 137), and PH-98108 sensors, were assembled with the aid of a microcontroller and personal computer to become a meat freshness detection apparatus. After being calibrated, the apparatus was then used to evaluate the freshness of the chicken meat sample. The results indicated that the apparatus showed satisfactory performance in detecting the freshness of the chicken meat sample. This apparatus was movable, simple, cheap, easy to operate, and suitable to be used by meat sellers or related institutions. The sensors used were capable of detecting the changes in colour, pH, NH3 gas, and H2S of the sample. The parameters of L*, b*, pH, H2S, and NH3 gas effectively detected the freshness of chicken meat. After 12 hrs of storage, the values of L*, b*, pH, H2S, and NH3 gas of the sample were 50.34, 17.26, 6.59, 134.08 ppm, and 42.34 ppm, respectively. Â© 2023 The Authors. Published by Rynnye Lyan Resources.